From green marketing to brand loyalty: Millennial Starbucks consumer perspective - Gede, I Gusti Ketut; Lasmini, Ni Ketut; Rumini, Ni Luh Putu Inten; Wijayati, Ni Luh Made; Narti, Ni Ketut (International research journal of management, IT and social sciences, 2022)
Currently, many companies have implemented green marketing activities in their various activities as part of their social awareness and they are required to reach consumers with green marketing messages in an effort to increase brand loyalty and raise environmentally friendly issues. Starbucks is one of the global companies that implement this. The purpose of this study was to examine the effect of green marketing on Starbucks’ brand loyalty. The population in this study is all Starbucks consumers in the millennial generation. In this study, the sample selection technique used a purposive sampling technique of 100 respondents. The analysis technique is simple linear regression analysis. The results of the analysis show that green marketing has an effect on brand loyalty.